The Effect of the Addition of Fermented Natural Lactic Acid Bacterial Liquid and Some Lactic Acid Bacterial Inoculants on Alfalfa Silage Quality, In Vitro Digestibility and Gas Production - Sadık Serkan Aydın (Journal of Agricultural Sciences)
This study was conducted to evaluate the effect of adding fermented natural lactic acid bacteria (PFJ) obtained from different sources and some lactic acid bacteria inoculants to alfalfa (Medicago sativa L.) silage on fermentation, in vitro organic matter digestibility (IVOMD) and in vitro gas production. In the study, (i) pure alfalfa plant constituted the control group, whereas (ii) 2% molasses added group (iii) PFJ (3% molasses) prepared from alfalfa + 2% molasses to alfalfa plant, (iv) PFJ (3% molasses) prepared from meadow grass + 2% molasses alfalfa. plant, (v) PFJ (3% Molasses) prepared from maize + 2% molasses to alfalfa plant, (vi) homofermentative added group + 2% molasses to alfalfa plant, (vii) heterofermentative group + 2% molasses to alfalfa plant, added groups formed the trial groups. Homofermentative and heterofermentative LAB inoculants were added to alfalfa plant at the level of 108 cfu/kg. When the DM, CA, ADF, NDF, IVOMD, ME and CH4 values of the prepared silages were examined, the differences between the groups were found to be statistically significant. When the fermentation characteristics (pH, NH3-N, CO2, LA, AA, BA, mold) of the silages prepared by adding PFJ and some LAB inoculants to alfalfa plant, the differences between groups were found to be statistically significant. When examined in terms of all parameters, it was determined that the addition of PFJ (3% molasses) prepared from meadow grass + 2% molasses to alfalfa plant had positive effects on silage quality, fermentation characteristics and in vitro organic matter digestion.